Randomised controlled trial of intravenous magnesium sulfate versus terbutaline for children in the management of acute exacerbation of asthma - Arif Zulqarnain,; Ayesha Fayyaz,; Muhammad Tariq Aziz,; Muhammad Salman Zafar, (Journal of the Pakistan Medical Association, 2026)
Objectives: To compare the effectiveness and safety of intravenous magnesium sulfate versus terbutaline in children with acute asthma exacerbations. Method: This randomised controlled trial was conducted at the Paediatric Department of The Children’s Hospital and Institute of Child Health, Multan, Pakistan, from January to August 2024, and comprised children o either gender aged 5-12 years who had a history asthma for a minimum six months, and presented with acute exacerbation of asthma requiring emergency treatment. The patients were randomly allocated to group A receiving intravenous magnesium sulfate and group B receiving intravenous terbutaline. After four hours of treatment, the response to treatment was measured on the basis of peak expiratory flow rate, oxygen saturation, heart rate and respiratory rate. Data was analysed using SPSS 26. Results: Of the 120 children, 62(51.7%) were girls. The overall mean age was 8.40±2.41 years. Post-treatment peak expiratory flow rate, oxygen saturation, heart rate, tachycardia and need for hospitalisation values were significantly better in group A compared to group B (p<0.05). Conclusion: Intravenous magnesium sulfate was more effective and safer than terbutaline in the management of acute asthma exacerbations in children. Trial Registration Number: NCT06626620. Key Words: Asthma, Heart rate, Peak expiratory flow rate, Respiratory rate, Terbutaline.